CHARACTERIZATION OF SURFACE WATER AND GROUNDWATER IN THE DAMASCUS GHOTTA BASIN: HYDROCHEMICAL AND ENVIRONMENTAL ISOTOPES APPROACHES - Kattan Z. (My University, 2006)
The hydrochemistry of major ions and environmental isotope compositions (18O, 2H and tritium) of water samples have been used to investigate the characteristics of rainfalls, surface water and groundwater in the Damascus Ghotta basin. The groundwater salinity in the Damascus Ghotta basin gradually increases, as the groundwater moves from western to south-eastern and north-eastern parts of the basin. A strong relationship exists between the Barada river and the surrounded groundwaters, mainly in terms of recharge by infiltration of surface waters. The groundwater quality in the Adra region has clearly become less saline as a result of establishment of the sewage-water-treatment station in this area since 1997. The uncommon depleted stable isotope concentrations in the vicinity of Al-Ateibeh Lake and Adra valley could be interpreted as a result of sub-flow recharge from the Cenomanian–Turonian aquifer, mostly prolonged along the Damascus Fault, which forms direct contact between this complex and the Quaternary alluvium aquifers. The extensive exploitation of water from the Cenomanian–Turonian aquifer for drinking water supply would shortly be reflected by a gradual decline of the groundwater table in the Damascus Ghotta basin. Amelioration of water quality in the Damascus basin still requires further management strategies and efforts to be taken within the forthcoming years.
Keywords: HYDROLOGY; GROUNDWATER; HYDROCHEMISTRY; ENVIRONMENTAL ISOTOPES; DAMASCUS BASIN; SYRIA; Quaternary; Turonian; Cenomanian; Cenozoic::Quaternary; Кайнозой::Четвертичная; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая::Верхний::Сеноманский